2013
DOI: 10.1002/ece3.764
|View full text |Cite
|
Sign up to set email alerts
|

What remains from a 454 run: estimation of success rates of microsatellite loci development in selected newt species (Calotriton asper, Lissotriton helveticus, and Triturus cristatus) and comparison with Illumina‐based approaches

Abstract: The development of microsatellite loci has become more efficient using next-generation sequencing (NGS) approaches, and many studies imply that the amount of applicable loci is large. However, few studies have sought to quantify the number of loci that are retained for use out of the thousands of sequence reads initially obtained. We analyzed the success rate of microsatellite loci development for three amphibian species using a 454 NGS approach on tetra-nucleotide motif-enriched species-specific libraries. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…RADseq; Davey and Blaxter 2011), identifying SSRs from longer read sequence data (e.g. Drechsler et al 2013;Wei et al 2014), or restricting shotgun Seq-to-SSR searches to so called ''Best PALs'' ([6 repeats for 4-6 mers; Castoe et al 2012a) when researchers need to perform population genetics assessments using NGS with limited resources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RADseq; Davey and Blaxter 2011), identifying SSRs from longer read sequence data (e.g. Drechsler et al 2013;Wei et al 2014), or restricting shotgun Seq-to-SSR searches to so called ''Best PALs'' ([6 repeats for 4-6 mers; Castoe et al 2012a) when researchers need to perform population genetics assessments using NGS with limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…The use of unassembled reads is a timesaving characteristic (Castoe et al 2012a;Lance et al 2013), however, several studies have cautioned against this approach when using short read data, such as from the Illumina platform. These studies have found that Illumina paired-end identified microsatellite loci can have an order of magnitude smaller success rate (in terms of amplification across multiple individuals and sequencing error) than those loci identified from longer 454 or PacBio reads (Drechsler et al 2013;Wei et al 2014). Despite this, the use of PALFINDER to identify SSR loci from short, unassembled Illumina reads is widespread (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of higher resolution markers such as microsatellites (e.g. Drechsler et al 2014;Valbuena-Ureña et al 2014) and a range-wide sampling of all populations combined with promising new methods (e.g. Dubey et al 2013;Pfenninger et al 2012) should provide improved insights into the effects of climate change on the loss of genetic diversity and evolutionary history in C. asper from the Pyrenees.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%